Engineered bamboo structures : proceedings of the Sustainable Bamboo Building Materials Symposium of BARC 2018 & the 3rd International Conference on Modern Bamboo Structures (ICBS 2018), June 25-27, 2018, Beijing, China /: proceedings of the Sustainable Bamboo Building Materials Symposium of BARC 2018 & the 3rd International Conference on Modern Bamboo Structures (ICBS 2018), June 25-27, 2018, Beijing, China. (2018) - Unknown
No abstract available